Functional diversification of Arabidopsis SEC1-related SM proteins in cytokinetic and secretory membrane fusion - Karnahl, Matthias (Proc Natl Acad Sci U S A, 2018)
Sec1/Munc18 (SM) proteins contribute to membrane fusion by interacting with Qa-SNAREs or nascent trans-SNARE complexes. Gymnosperms and the basal angiosperm Amborella have only a single SEC1 gene related to the KEULE gene in Arabidopsis. However, the genomes of most angiosperms including Arabidopsis encode three SEC1-related SM proteins of which only KEULE has been functionally characterized as interacting with the cytokinesis-specific Qa-SNARE KNOLLE during cell-plate formation. Here we analyze the closest paralog of KEULE named SEC1B. In contrast to the cytokinesis defects of keule mutants, sec1b mutants are homozygous viable. However, the keule sec1b double mutant was nearly gametophytically lethal, displaying collapsed pollen grains, which suggests substantial overlap between SEC1B and KEULE functions in secretion-dependent growth. SEC1B had a strong preference for interaction with the evolutionarily ancient Qa-SNARE SYP132 involved in secretion and cytokinesis, whereas KEULE interacted with both KNOLLE and SYP132. This differential interaction with Qa-SNAREs is likely conferred by domains 1 and 2a of the two SM proteins. Comparative analysis of all four possible combinations of the relevant SEC1 Qa-SNARE double mutants revealed that in cytokinesis, the interaction of SEC1B with KNOLLE plays no role, whereas the interaction of KEULE with KNOLLE is prevalent and functionally as important as the interactions of both SEC1B and KEU with SYP132 together. Our results suggest that functional diversification of the two SEC1-related SM proteins during angiosperm evolution resulted in enhanced interaction of SEC1B with Qa-SNARE SYP132, and thus a predominant role of SEC1B in secretion.